Surgical Bailout Therapy after Implantation of a Medtronic CoreValve Bioprosthesis. (9th August 2012) - Calé, Rita; Neves, José; Teles, Rui; Brito, João; Abecasis, Miguel; Almeida, Manuel; Nolasco, Tiago; Mendes, Miguel
Abstract : Moderate-to-severe paraprosthesic leak causing hemodynamic deterioration and left ventricular remodeling can occur after transcatheter aortic valve implantation (TAVI). We present the case of a 75-year-old woman who underwent TAVI with a 26 mm CoreValve prosthesis complicated with an acute left ventricle dilatation due to a severe paravalvular leak. Patient was unresponsive to elective balloon post-dilatation, and therefore she was successfully treated with open-heart surgery to remove the malfunctioning CoreValve bioprosthesis and perform standard aortic valve replacement.